Proteolytic cleavage of p53 mutants in response to mismatched DNA - Mee, T (Nature Publishing Group, 1999)
Interaction of p53 with mismatched DNA induces proteolytic cleavage with release of a 35-kDa protein fragment from the p53–DNA complexes. The 35-kDa cleavage product is activated for specific biochemical function(s) and may play a role in the cellular response to DNA damage (Molinari et al (1996) Oncogene13: 2077–2086; Okorokov et al (1997) EMBO J16: 6008–6017). In the present study we have asked if mutants of p53 retain the ability to undergo similar proteolytic cleavage, and compared sequence-specific ‘DNA contact’ with ‘structural’ mutants commonly found in human cancer. In addition, a series of phosphorylation site mutants were generated to investigate the possible effects of phosphorylation/dephosphorylation on the proteolytic cleavage of p53. All mutants tested bound to a mismatched DNA target in vitro. Moreover, studies in vitro and in vivo indicate that p53 mutants with intact conformational structure (as determined by immunoreactivity with PAb246 and PAb1620) retain the ability to undergo proteolytic cleavage similar, if not identical, to the wild-type p53 protein. Our results suggest that the capacity for p53 to bind mismatched DNA is independent of structural conformation of the central core domain. Proteolytic cleavage, however, is crucially dependent upon a wild-type conformation of the protein. © 1999 Cancer Research Campaign